Interaksi Antara Profitabilitas, Likuiditas dan Aktivitas Pada Keputusan Investasi - Rustan DM (STIE AMKOP, 2022)
This study aims to determine the effect of profitability, liquidity and activity on investment decisions. This research is an associative research. This research was conducted on Oil and Gas companies listed on the Indonesia Stock Exchange for the period 2014 to 2021 through the internet using the www.idx.com website and from the respective websites of the Oil and Gas companies studied. The population in this study were all Oil and Gas companies listed on the Indonesia Stock Exchange from 2012-2019. There are 9 oil and gas companies listed on the Indonesia Stock Exchange. The sample is determined by considering the number of samples used is 32 observation samples. The results of the study found that profitability, liquidity and activity have a positive and significant impact on investment decisions in oil and gas companies listed on the Indonesia Stock Exchange. Keywords: Profitability, Liquidity, Activity, Investment Decisions .